MALADMINISTRATION AND INTENTIONALITY ON THE CRIMINAL CORRUPTION COURT IN INDONESIA - Elstonsius Banjo; Surastini Fitriasih; Eva Achjany Zulfa (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2022)
Maladministration and state financial losses have been the basis of the Criminal Court of Corruption’s decision to punish the defendant. Judges' decisions are often based on proven objective facts while subjective facts, including the